2022
DOI: 10.3390/s22239558
|View full text |Cite
|
Sign up to set email alerts
|

Balance Impairments in People with Early-Stage Multiple Sclerosis: Boosting the Integration of Instrumented Assessment in Clinical Practice

Abstract: The balance of people with multiple sclerosis (PwMS) is commonly assessed during neurological examinations through clinical Romberg and tandem gait tests that are often not sensitive enough to unravel subtle deficits in early-stage PwMS. Inertial sensors (IMUs) could overcome this drawback. Nevertheless, IMUs are not yet fully integrated into clinical practice due to issues including the difficulty to understand/interpret the big number of parameters provided and the lack of cut-off values to identify possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Changes in balance and gait initiation are seen in early-stage patients due to alteration of motor modulation of stance limb kinetics during gait initiation. 27 Finally, exercise-induced gait deterioration is an early symptom that limits ambulation, becoming more prominent with increasing neurological disease and also observed with the get-up and go test. 28,29 Limb numbness and weakness (L): Motor deficits and muscle function impairment are cardinal features of MS from the beginning of the disease.…”
Section: Vision (Visi)mentioning
confidence: 99%
“…Changes in balance and gait initiation are seen in early-stage patients due to alteration of motor modulation of stance limb kinetics during gait initiation. 27 Finally, exercise-induced gait deterioration is an early symptom that limits ambulation, becoming more prominent with increasing neurological disease and also observed with the get-up and go test. 28,29 Limb numbness and weakness (L): Motor deficits and muscle function impairment are cardinal features of MS from the beginning of the disease.…”
Section: Vision (Visi)mentioning
confidence: 99%
“…While suggested as suitable for remote MS monitoring 77 , measures can be different in unsupervised settings 75 . Over and above, authors in 78 highlighted that PwMS showed a reduction in sway complexity paired with an increase in sway intensity while performing an altered Romberg test (patient stands on foam), which could point to a less automatic postural control strategy, albeit the correlation between EDSS and balance scores was only significant for EDSS > 3 78 .…”
Section: Imu and Motion Capturementioning
confidence: 99%
“…To address these challenges, studies have shown that postural sway can be assessed using data from just a sacral or chest accelerometer [ 10 ], [ 14 ], [ 15 ], [ 16 ]. Sensor-derived postural sway measures have been used to classify fall risk in PwMS [ 14 ], distinguish between disease states [ 10 ], [ 13 ], [ 16 ], [ 17 ], [ 18 ] and to augment current assessment techniques [ 19 ], thereby achieving similar clinical utility to the force platform.…”
Section: Introductionmentioning
confidence: 99%